انخفاض الثقة بالنفس وآثاره على أداء العرض الشفوي بين طلاب اللغة الانجليزية كلغة أجنبية في كلية التربية، يفر ن - أبو نواس بسمة العموري الشروقي سعيد (مجلة الاصالة, 2026)
The present research was conducted to investigate the effect of self-confidence on improving oral presentation performance among English foreign language students at the College of Education in Yefren. The sample included 32 students. This research aimed to identify the challenges which students may face during oral presentations and reveal the effective techniques they have to use in order to improve their oral performance. The study adopted a descriptive-quantitative approach using a questionnaire. The results demonstrated the important role of self-confidence for students in organizing ideas, interacting with an audience, and improving their overall performance. It also revealed that many students face obstacles prevent them from reaching full potential in this area. However, those who incorporate new effective strategies in to their presentations are mor confident. In the light of success of this study, Libyan educational organizations should concentrate efforts to support students and community in providing structured training programs and adequate technological resources in order to develop student’s presentation performance.